The Dominus Litis Principle and the Public Prosecutor's Interest in Case Control - Achmad Yani; Mispansyah Mispansyah; Ahmad Syaufi (International Journal of Sociology and Law, 2025)
The Public Prosecutor holds a central role in the criminal justice system as the primary controller of the prosecution process. This authority is based on the fundamental principle of Dominus Litis, which literally translates to "master of the case." This paper aims to deeply analyze the implementation of the Dominus Litis principle and to examine the various interests underlying the Public Prosecutor's authority in controlling a criminal case. Using a normative juridical research method with a literature and conceptual approach, this study investigates how the principle legitimizes the prosecutor's power to determine whether a case is suitable for trial, to terminate it, or to resolve it through alternative mechanisms. The analysis reveals that the prosecutor's interest in case control is not merely limited to technical-juridical aspects but also encompasses broader considerations such as the public interest, law enforcement efficiency, and the achievement of restorative justice. While granting significant discretion, this absolute authority also raises discourse on the importance of effective oversight mechanisms to prevent potential abuse of power and ensure accountability. It is concluded that the implementation of the Dominus Litis principle must always be balanced with transparency and objectivity to ensure that case control by the prosecutor genuinely aims to achieve substantive justice